Maternal Depressive Symptoms and Their Association with Breastfeeding and Child Weight Outcomes - María Pineros-Leano; Jaclyn A. Saltzman; Janet M. Liechty; Salma Musaad; Liliana Aguayo (MDPI AG, 2021)
Children of mothers with depressive symptoms are at a higher risk for psychosocial, behavioral, and developmental problems. However, the effects of maternal depression on children's physical growth are not well understood. To address the gaps in the literature, this study examined the association between maternal depressive symptoms, breastfeeding behaviors, and child weight outcomes. Data from 204 mother-child dyads who participated in the STRONG Kids 1 Study were used. Mothers and children were assessed twice when the children were 3 and 4 years old. Height and weight measurements of children and mothers were collected by trained researchers during both assessments. Multiple linear regression and analysis of covariance tests were used to examine the associations between maternal depressive symptoms, breastfeeding, and age and sex-adjusted child body mass index percentile. Recurrent maternal depressive symptoms when the child was 3 and 4 years old were not associated with child body mass index percentiles (BMI-P) at age 4. Mothers who breastfed for at least 6 months had significantly lower depressive symptoms when their children were 3 years of age, but the differences did not persist at age 4. In this community sample, maternal depressive symptoms were not associated with child BMI-P, regardless of breastfeeding duration.